Purification of Phage Cocktail and its Inhibition Spectrum to Foodborne Disease Bacteria - Nindita, Lia Oriana; Wardani, Agustin Krisna (Jurnal Teknologi Pertanian, 2013)
The aim of this research is to purify a phage cocktail to obtain a single phage and evaluate the broad host range of a single phage. The obtained single phage (Ð¤LA-1), was found to attack strains of Shigella flexneri, Shigella dysentri, Eschericia coli, Salmonella thypi, and Listeria monocytogenes, but not members of the strains Staphylococcus aureus, Bacillus cereus and Lactobacillus plantarum. The data showed that Ð¤LA-1 is moreÂ  effective to attack the Shigella flexneri than other strain with the burst size of 1.37.108 PFU/ml. ItÂ  can reduced the cell numbers of their positive bacteria targets after 8 hr. The complete nucleotide sequence of the genome 21226 basepairs of Ñ„LA-1 was determined. Keywords: purification, phage cocktail, plaque, pathogen bacteria, foofdborne disease